Hardware Trojans detection based on projection pursuit - Peng ZHANG; Xin-cheng WANG; Qing ZHOU (Tongxin xuebao)
A novel hardware Trojans detection technique using the side channel signals of chips was proposed.Based on the projection pursuit with absolute information divergence index,this technique could find out the data structure enables reflect high dimension special rules without obvious i tion loss,so as to attain the goal of feature abstraction and identification on side channel signals of IC chips.The detection experiment against an exemplary AES-128 hardware Trojan circuit showed that the technique could distinguish the difference of side channel signal's feature between the genuine chip and tested chip,and consequently could detect the existence of the hardware Trojan.